A flexible polymer-based Li–air battery using a reduced graphene oxide/Li composite anode. Issue 14 (21st March 2018) - Guo, Ziyang; Li, Jinli; Xia, Yuan; Chen, Chao; Wang, Fengmei; Tamirat, Andebet Gedamu; Wang, Yonggang; Xia, Yongyao; Wang, Lei; Feng, Shouhua
Abstract : Belt-shaped Li–air batteries using 4% SiO2 –LiI-GPE with an rGO/Li anode display superior electrochemical performance under different harsh bending conditions. Abstract : Flexible Li–air batteries have been proposed as a potential power source for next-generation flexible electronics due to their super-high theoretical energy density. However, the safety problems derived from dendritic-deposition and high-activity of a Li anode and the leakage and volatilization of liquid electrolyte severely impede their practical application. Herein, we design a flexible belt-shaped Li–air battery with high stability and safety, which is constructed by using a reduced graphene oxide (rGO)/Li anode, gel polymer electrolyte containing LiI and 4 wt% SiO2 (4% SiO2 –LiI-GPE). The rGO/Li anode shows lower mass density, better toughness and less dendrite growth compared with a pure Li anode. Additionally, 4% SiO2 –LiI-GPE has a high ionic conductivity of 1.01 mS cm −1, flame-resistant polymer matrix, excellent protective effect on the Li anode and no-leakage properties. Furthermore, the synergy of the LiI and SiO2 additives promotes the decomposition of discharge products and improves the safety of the battery at the same time. As a result, this belt-shaped Li–air battery can steadily run for 100 cycles with a small average overpotential of ∼1.45 V in ambient air (relative humidity of 15%) under different mechanical deformations. Moreover, its voltage curves over operation could remain almost unchanged under a series of bending conditions.